Analisis Kelayakan dan Sensitivitas Usaha Home Industri Tempe di Desa Rambipuji Kecamatan Rambipuji Kabupaten Jember - Mahdi Ami, Agus; Wahyu Pudjiastutik, Endang (Program Studi Agribisnis, 2024)
Agroindustry is a combination of agriculture and industry. Tempe industry is one of the potentian food processing industries to be defeloped. This study aims to find out how much Ferdi’s tempeh business income is, and to find out the feasibility of Mr.Ferdi’s tempeh business. The research location was chosen purposively with several considerations. This research method uses descriptive method using primary and secondary data. Based on the results of the business analysis, it is feasible to work on it. And the results of the sensitivity analysis show that the business in sensitive to changes in interest rates